The inflation accelerator - Andrés Blanco; Corina Boar; Callum Jones; Virgiliu Midrigan (Federal Reserve Bank of Atlanta, 2024)
We develop a tractable sticky price model in which the fraction of price changes evolves endogenously over time and, consistent with the evidence, increases with inflation. Because we assume that firms sell multiple products and choose how many, but not which, prices to adjust in any given period, our model admits exact aggregation and reduces to a one-equation extension of the Calvo model. This additional equation determines the fraction of price changes. The model features a powerful inflation accelerator-a feedback loop between inflation and the fraction of price changes-that significantly increases the slope of the Phillips curve during periods of high inflation. Applied to the U.S. time series, our model predicts that the slope of the Phillips curve ranges from 0.02 in the 1990s to 0.12 in the 1970s and 1980s.
Keywords: E31; E32; E52; 330; Phillips curve; inflation; price rigidities